Interventions for Improving Young Children’s Dietary Intake through Early Childhood Settings: A Systematic Review - Bell, Lucinda K.; Golley, Rebecca K. (International Journal of Child Health and Nutrition, 2015)
Early childhood settings (ECS) offer a unique opportunity to intervene to improve children’s nutrition. This paper reviews the literature on early childhood setting interventions that aim to improve children’s dietary intake. Environmental and individual determinants of children’s dietary intakes were also investigated. Prospective intervention studies targeting centres, staff, parents/caregivers or children, were reviewed. Methodological quality was assessed. Twenty six studies (14 weak, 12 moderate quality) were included. Interventions were delivered primarily via training workshops and/or written materials. Study findings favoured intervention effectiveness in 23 studies. Improvements were seen in children’s intake for 8 out of 11 studies assessing dietary intake outcomes. Small increases in fruit and vegetable consumption were observed in five studies. Most studies measuring parental or centre food provision observed post-intervention improvements across a number of food groups, including fruit, vegetables, whole grains and sweetened beverages. Significant improvements in child, parent and/or staff knowledge, attitudes or behaviours were observed consistently across studies. For those studies that included a comparison group, these improvements were observed only in the intervention group. ECS interventions can achieve changes in children’s dietary intake and associated socio- environmental- determinants, although the quality of current research limits confidence in study findings. Future intervention development needs to carefully consider the behavioural targets, modifiable determinants and utilise age-appropriate and effective behaviour change theory, in addition to inclusion of dietary intake outcomes.